KAJIAN PEMBERIAN KOMPOS DARI KULIT BUAH KAMANDRAH TERHADAP PERTUMBUHAN BIBIT TANAMAN KAMANDRAH (Croton tiglium L.) YANG DITANAM PADA TANAH BEKAS TAMBANG - Sudyana I Nyoman; Saputera Saputera; Muliansyah Muliansyah; Atikah Titin Apung (AgriPeat, 2015)
The purpose of this study was to determine the effect of increasing doses of kamandrah rind composting on the growth of kamandrah seedlings planted on former mining soil. The materials used for this study were kamadrah seeds taken from Tamiang, dolomite lime, compost , polybag, former mining soil, wood, nail and and gauze. The tools used were scales, hoes, machetes, yells, sieves, and other stationeries. This study simply employed a Completely Randomized Design (CRD) with 4 levels of treatment K0 (control), K1 (composting with 2 t / ha), K2 (composting with 4 t / ha) and K3 (composting with 6 t / ha). The series of experiments for each level of treatment was repeated for six times, so that the overall result were 24 experimental units. The results showed that the composting application of kamandrah seedlings has a significant effect on the height of plant, the number of leaves, the seedlings. The of kamandrah rind composting was best applied on the treatment of K2 that resulted in 14,11 cm for the height of the plant, 9.71 for the number of leaves, 9.26 g for the fresh weight and 1.36 g for the dry weight of the fruits, those were higher than the other treatme